Ultra-high temperature multi-component shape memory alloys. (1st January 2019) - Canadinc, Demircan; Trehern, William; Ma, Ji; Karaman, Ibrahim; Sun, Fanping; Chaudhry, Zaffir
Abstract: This paper presents martensitic transformation characteristics of selected multi-component (Ni, Pd)50 (Ti, Hf, Zr)50 alloys, with an emphasis on superelasticity and thermal actuation behavior. We report, for the first time, austenite finish temperatures beyond 700 °C in NiTi-based high temperature shape memory alloys without the presence of platinum and gold. The increase in transformation temperatures, and transformation stress and recovered strains at elevated temperatures are attributed to the high configurational entropy of the studied alloys. Based on the current findings, we introduce multi-component ultra-high temperature shape memory alloys, which are expected to pioneer a completely new field of study and applications for shape memory alloys. Graphical abstract: Unlabelled Image